Math 350
Advanced Calculus I
Fall 2009
Homework Solutions
Section 11
ORDERED FIELDS
11.3
Let
x
,
y
, and
z
be real numbers. Prove the following.
(a)
−
(
−
x
) =
x
Proof:
The element
−
(
−
x
) is by deFnition the additive inverse of
−
x
. To show
−
(
−
x
) =
x
,
we need to show that
x
is the additive inverse of
−
x
. By Axiom A5, the additive inverse of
any element is unique, so to show that
x
is the additive inverse of
−
x
, we only need to show
that
x
behaves like the additive inverse of
−
x
. That is, we need to show
(
−
x
) +
x
= 0
.
By Axiom A5, since
−
x
is the additive inverse of
x
, then
x
+ (
−
x
) = 0
.
By Axiom A2 Commutative Law of Addition,
x
+ (
−
x
) = (
−
x
) +
x.
Therefore
(
−
x
) +
x
= 0
,
as required. Thus
−
(
−
x
) =
x
.
(b)
(
−
x
)
·
y
=
−
(
xy
) and (
−
x
)
·
(
−
y
) =
xy
Proof:
The element
−
(
xy
) is by deFnition the additive inverse of
xy
.
So, to show that
(
−
x
)
·
y
=
−
(
xy
), we need to show that (
−
x
)
·
y
behaves like the additive inverse of
xy
. That
is, we need to show
xy
+ (
−
x
)
·
y
= 0
.
We have
xy
+ (
−
x
)
·
y
=
yx
+
y
·
(
−
x
)
=
y
[
x
+ (
−
x
)]
=
y
·
0
= 0
by M2 Commutative Law
by DL Distributive Law
by A5 Existence of Additive Inverses
by Theorem 11.1(b)
Alternatively, we can use the result of Theorem 11.1(c). We have
(
−
x
)
·
y
= [(
−
1)
·
x
]
·
y
= (
−
1)
·
(
x
·
y
)
=
−
(
xy
)
by Theorem 11.1(c)
by M3 Associative Law
by Theorem 11.1(c)
To prove (
−
x
)
·
(
−
y
) =
xy
, we can use the Frst result. We have
(
−
x
)
·
(
−
y
) =
−
[
x
·
(
−
y
)]
=
−
[(
−
y
)
·
x
]
=
−
[
−
(
yx
)]
=
−
[
−
(
xy
)]
=
xy
by the Frst part of (b)
by M2 Commutative Law
by the Frst part of (b)
by M2 Commutative Law
by part (a)
12
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentMath 350 Homework Solutions page 13
Section 11
•
Ordered Fields
11.3
(continued)
(e)
If
x
6
= 0, then
x
2
>
0.
Proof:
Suppose
x
6
= 0. We need to show
x
2
>
0
.
By Axiom O1 Trichotomy Law, exactly one of the relations
x
= 0,
x >
0, or
x <
0 holds.
Since
x
6
= 0 by assumption, it follows that either
x >
0 or
x <
0. We need to prove
x
2
>
0 in
both of these cases.
Case 1.
Suppose
x >
0.
By Axiom O4, since
x >
0, when we multiply both sides of the
inequality
x >
0 by
x
, we preserve the inequality, so we obtain
x
2
=
x
·
x > x
·
0
.
By Theorem 11.1(b),
x
·
0 = 0, so this implies
x
2
>
0, as required.
Case 2.
This is the end of the preview. Sign up
to
access the rest of the document.
 Spring '08
 QIAN
 Calculus, Real Numbers

Click to edit the document details